Synergistic Coupling of Ether Electrolyte and 3D Electrode Enables Titanates with Extraordinary Coulombic Efficiency and Rate Performance for Sodium‐Ion Capacitors. Issue 2 (17th October 2018) - Gui, Qiuyue; Ba, Deliang; Zhao, Zhenshuai; Mao, Yanfang; Zhu, Weihua; Lei, Tianyu; Tan, Jianfeng; Deng, Bohua; Xiao, Liang; Li, Yuanyuan; Liu, Jinping
Abstract: Sodium‐ion capacitors (SICs) have attracted increasing attention for sustainable energy utilization owing to their low cost and similar intercalation electrochemistry with lithium‐ion capacitors. However, the practical application of SICs is seriously hindered by the low initial coulombic efficiency (ICE) and limited redox kinetics at the battery electrode side. Herein, taking a layered sodium titanate battery anode as an example, this study reports on the synergistic combination of ether electrolyte and binder‐free array architecture to simultaneously achieve superior ICE and ultrafast Na + intercalation. The resulting Na2 Ti2 O5 nanosheet array anode delivers extraordinary ICE (91%), high cycle CE (≈100%), and outstanding rate performance (66% capacity retention at 120 C). The key to the superior performance lies in the synergistic promotion between electrolyte and 3D electrode architecture, which ensures a very thin and stable solid‐electrolyte interphase, largely reduced resistances, and fully accessible interlayers for Na + . Moreover, a SIC device is assembled with an Na2 Ti2 O5 array anode and a commercial activated carbon cathode, exhibiting high ICEs (80–90%) at various current densities, high energy densities (54.5 Wh kg −1 ; 17.2 mWh cm −3 ), and ultralong cycling stability (>10 000 cycles). This work presents an advanced concept for designing high‐CE and high‐rate battery electrodes for a variety of sodium ion energy storage systems. Abstract : Synergistic coupling of ether electrolyte and 3D binder‐free array architecture endows layered titanate anode simultaneously with superior initial coulombic efficiency (ICE: 91%) and ultrafast Na + intercalation kinetics (120 C rate). With such an anode, a sodium ion capacitor is further assembled, exhibiting high CEs (80–90%) and ultralong cycling stability up to 10 000 times.